Software e-inventory management system / Chew Kok Seng - Chew , Kok Seng (2003)
Inventory has been part and parcel of business since its existence. And through generations, many inventory management systems have been developed in order to cope up with the ever-growing business world. With the invention of computer, the business world went into a breakthrough to more organized, efficient and systematic way of handling and integrating all areas of business, thus enhancing the ability of Enterprise Resource Planning. Improvement did not stop, yet it went another peak when web technology and networking grew popular throughout the world. With the emergence of E-commerce,E-business and globalization, the dream of business without boundary has become a reality. Based on the concepts of E-commerce and Enterprise Resource Planning (ERP) strategy, this project is to build a web-based e-inventory Management System (Software). The purpose of this project is to build an enhanced enterprise's inventory management system for all the Information Technology and Communication(ICT) companies in Malaysia. Any user on any platform at ant time will be able to retrieve or upload software inventory information through this system. This system will provide the control& management of inventory, ensuring the sufficiency of inventory, accuracy of data keeping and more profitable relationship with supplier. In order to produce a more efficient and better quality system, this project will be develop through several stages, by implementing the Waterfall Model methodology. The first to stage, which are requirements analysis and system design will be completed in the first semester. While for system coding, system testing, and system operation is completed in the second semester. This methodology approach was chosen because a web-based management system needs a well organized and structured planning of system design and implementation. Finally, this inventory system will be integrated with other sub-system in the enterprise to provide a fully integrate inventory utilities. The order module (beside e- Inventory(Software) the involved is: e-Inventory Management System (Hardware).